Time-dependent decrease in fault strength in the 2011–2016 Ibaraki–Fukushima earthquake sequence. Issue 2 (21st September 2022) - Wimpenny, Sam; Forrest, Natalie; Copley, Alex
SUMMARY: Two near-identical M w 5.8 earthquakes in 2011 and 2016 ruptured the Mochiyama Fault in the Ibaraki–Fukushima region of Japan. The unusually short repeat time between the two earthquakes provides a rare opportunity to estimate the evolution of stress on a fault through an earthquake cycle, as the stress drop in the first earthquake provides a reference value from which we can infer variations through time in the stresses required to cause earthquake rupture. By combining observations of crustal deformation from GPS, InSAR and seismology with numerical models of stress transfer due to coseismic deformation and post-seismic relaxation, we demonstrate that the rupture area on the Mochiyama Fault could only have been reloaded by up to 50–80 per cent of the 2011 earthquake stress drop (3–10 MPa) between that event and the subsequent 2016 earthquake. Most of this reloading was caused by afterslip around the rupture area driven by stress changes from the 2011 Mochiyama and Tohoku-oki earthquakes. We therefore infer that the Mochiyama Fault became weaker in the intervening 6 yr, with at least a 1–5 MPa drop in the shear stresses needed to break the fault in earthquakes. The mechanism(s) that led to this weakening are unclear, but were associated with extensive aftershock seismicity that released a cumulative moment similar to the 2011 main shock. Temporal changes in fault strength may therefore play a role in modulating the timing of moderate-magnitude earthquakes.